Antifungal Activity Of Jackfruit Leaf Extract (Artocarpus heterophyllus Lam.) Againts The Growth of Candida albicans - Rahmawida Putri; Minarni ,; Epinur ,; Banu Kuncoro; Reza Sudrajat; Yusransyah , (BEST Journal (Biology Education, Sains and Technology), 2022)
Candidiasis is an infection that often occurs among all fungal infections involving the skin or mucous membranes. Most infections caused by Candida albicans. The use of synthetic antifungal poses a lot of problems such as serious side effects, resistance, complicate the rules of use, and the need for medical supervision. One of the plants that used as traditional medicine by the people of jackfruit leaves. This research was conducted to determine whether jackfruit leaves can provide the antifungal activity against Candida albicans. This research was carried out experimentally in the laboratory. Samples of dried jackfruit leaves are crushed and extracted by maceration using 96% ethanol and thickened with a rotary evaporator. Subsequently extract with a concentration of 1.25% (K1), 2.5% (K2), 5% (K3), 10% (K4), 20% (K5), 40% (K6) and 80% (K7), positive control 25 µg fluconazole (K8) and negative control DMSO (K9) tested antifungal activity against Candida albicans with agar diffusion method by way of pitting with 3 times replication. The result of research showed jackfruit leaves extract can provide the antifungal activity against Candida albicans with optimal concentration is 80% concentration. Kruskal Wallis test analysis results that each treatment group showed a significant difference (Sig 0.05). Tukey HSD Post Hoc test showed only K7 not showed a significant difference with the positive control (Sig 0.05).